A survey of continuous finite-time consensus algorithms in multi-agent systems. (2016) - Du, Haibo; Li, Hua; Wang, Xiangyu
This paper mainly reviews some results and progress on finite-time consensus via continuous feedbacks in multi-agent systems. Finite-time control theory has been applied to solve consensus problems in recent years, since finite-time stable systems usually possess faster convergent rate, and better robustness and disturbance rejection properties. First of all, some fundamental definitions about finite-time control and finite-time consensus are introduced. Then, some continuous finite-time algorithms are listed for first-order/second-order multiagent systems, multiple rigid spacecraft, multiple non-holonomic mobile robots, multiple under-water vehicle systems.